Tracheostomy during SARS‐CoV‐2 pandemic: Recommendations from the New York Head and Neck Society. Issue 6 (20th April 2020) - Miles, Brett A.; Schiff, Bradley; Ganly, Ian; Ow, Thomas; Cohen, Erik; Genden, Eric; Culliney, Bruce; Mehrotra, Bhoomi; Savona, Steven; Wong, Richard J.; Haigentz, Missak; Caruana, Salvatore; et al.
Abstract: The rapid spread of SARS‐CoV‐2 in 2019 and 2020 has resulted in a worldwide pandemic characterized by severe pulmonary inflammation, effusions, and rapid respiratory compromise. The result of this pandemic is a large and increasing number of patients requiring endotracheal intubation and prolonged ventilator support. The rapid rise in endotracheal intubations coupled with prolonged ventilation requirements will certainly lead to an increase in tracheostomy procedures in the coming weeks and months. Performing tracheostomy in the setting of active SARS‐CoV‐2, when necessary, poses a unique situation, with unique risks and benefits for both the patient and the health care providers. The New York Head and Neck Society has collaborated on this document to provide guidance on the performance of tracheostomies during the SARS‐CoV‐2 pandemic.